PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN PELANGGAN AIRLINES PENGGUNA JASA MRO PADA PT. GARUDA MAINTENANCE FACILITY AEROASIA TBK. (GMFAA) STATION DENPASAR - Ongki Prasetia; I Made Sumartana (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Ngurah Rai, 2020)
The purpose of this study is to determine whether service quality has a positive and significant effect on the satisfaction of airlines customers using MRO services at PT. Garuda Maintenance Facility Aero Asia Tbk. (GMFAA) Denpasar Station. Data sources are primary data and secondary data. The types of data used are quantitative and qualitative data. Data collection techniques used were observation, interviews, questionnaires and literature review. The analysis technique used is simple linear regression analysis, determination analysis and t-test. From the results of the study, there is a positive and significant influence on service quality which has a positive and significant effect on the satisfaction of airlines customers using MRO services at PT. Garuda Maintenance Facility Aero Asia Tbk. (GMFAA) Denpasar Station.